Establishing an expert mental health consumer research group: Perspectives of nonconsumer researchers. Issue 1 (28th April 2020) - Happell, Brenda; Gordon, Sarah; Roper, Cath; Ellis, Pete; Waks, Shifra; Warner, Terri; Scholz, Brett; Platania‐Phung, Chris
Abstract: Purpose: To explore the views and opinions of nonconsumer researchers to the concept of an Expert Consumer Researcher Group. Design and Methods: Qualitative exploratory involving individual interviews with nonconsumer mental health researchers experienced in working collaboratively with consumer researchers. Data were analyzed thematically. Findings: Participants viewed the concept positively, albeit with caution. Perceived advantages included: greater visibility and enhanced access; collegiality; sharing and creating expertise; broader acceptance; making it mandatory; and structure and location. Participants were concerned about potential tokenism and implementation barriers. Practice Implications: Consumer involvement enhances the quality and relevance of research, potentially impacting clinical practice.